The Implementation of Inquiry Learning to Improve Islamic Primary Students' Learning Outcome/Implementasi Pembelajaran Inkuiri untuk Meningkatkan Hasil Belajar Siswa Madrasah Ibtidaiyah - Desy Rini Mahmudah; Isna Nurul Inayati (STAI Ma'had Aly Al-Hikam Malang, 2021)
This research was motivated by the low learning outcomes of students in the fifth grade mathematics subject at Madrasah Ibtidaiyah Nahdlatul Ulama Bululawang in statistics material. The purpose of this study is to improve student learning outcomes through the inquiry method. This research uses Classroom Action Research (CAR) with a quantitative approach. The results of this study indicate that in the cognitive domain in the first cycle the class average reaches 69 with a completeness percentage of 65%. In cycle II the class average increased to 76 with the percentage of completeness of 74%. Whereas in the psychomotor domain in the first cycle an average of 88 with a completeness percentage of 78% and in the second cycle an average of increased to 95 with a percentage of 87% completeness. So it can be concluded that the implementation of the inquiry method can improve student learning outcomes.